ROLE AMBIGUITY VERSUS JOB EMBEDDEDNESS; MEDIATION OF INTERPERSONAL CONFLICT - Naeem, Kamran; Pervez, Anjum; Naeem, Imran; Lodhi, Sidra (The journal of contemporary issues in business and government, 2021)
The purpose of this study is to investigate the impact of role ambiguity and interpersonal conflict on job embeddedness. The study also investigates the mediating rolethat interpersonal conflict plays between role ambiguity and job embeddedness. Data for the study was obtained from the service sector organizations. Data collected from245 respondents usingvoluntary cross-sectional online survey method. The analysis was carried out using regression and process macro. Results revealed that interpersonal conflict at the workplace plays a reflective role between role ambiguity and job embeddedness. The results have also supported findings of previous literature. Besidesthis study making a theoretical contribution,it also provides an insight into various practical implications to practitioners.